Forms of Hatred : The Troubled Imagination in Modern Philosophy and Literature - Donskis, Leonidas (Brill Book Archive Part 1, ISBN: 9789004472495., 2003)
This book analyzes such symbolic designs of the modern troubled imagination as the conspiracy theory of society, deterministic concepts of identity and order, antisemitic obsessions, self-hatred, and the myth of the loss of roots. It offers, among other things, the unique East-Central European materials incorporated in a broad, imaginative synthesis and critique of contemporary social analysis.